Facilitating Residents' Understanding of Electronic Health Record Report Card Data Using Faculty Feedback and Coaching. (9th August 2022) - Sebok-Syer, Stefanie S.; Shaw, Jennifer M.; Sedran, Robert; Shepherd, Lisa; McConnell, Allison; Dukelow, Adam M.; Syer, Mark D.; Lingard, Lorelei
Abstract : Purpose: Feedback continues to present a challenge for competency-based medical education. Clear, consistent, and credible feedback is vital to supporting one's ongoing development, yet it can be difficult to gather clinical performance data about residents. This study sought to determine whether providing residents with electronic health record (EHR)-based report cards, as well as an opportunity to discuss these data with faculty trained using the R2C2 model, can help residents understand and interpret their clinical performance metrics. Method: Using action research methodology, the author team collected EHR data from July 2017 to February 2020, for all residents (n = 21) in one 5-year Emergency Medicine program and created personalized report cards for each resident. During October 6–17, 2020, 8 out of 17 eligible residents agreed to have their feedback conversations recorded and participate in a subsequent interview with a nonphysician member of the research team. Data were analyzed using thematic analysis, and the authors used inductive analysis to identify themes in the data. Results: In analyzing both the feedback conversations as well as the individual interviews with faculty and residents, the authors identified 2 main themes: (1) Reactions and responses to receiving personalized EHR data and (2) The value of EHR data for assessment and feedback purposes. All participants believed that EHR data metrics are useful for prompting self-reflection, and many pointed to their utility in providing suggestions for actionable changes in their clinical practice. For faculty, having a tool through which underperforming residents can be shown "objective" data about their clinical performance helps underscore the need for improvement, particularly when residents are resistant. Conclusions: The EHR is a valuable source of educational data, and this study demonstrates one of the many thoughtful ways it can be used for assessment and feedback purposes.